Modeling of yield, slope efficiency, and spectra of multisegment distributed feedback lasers. Issue 1 (1st December 2017) - Kim, Hong; Khinda, Gurvinder; Jules, Jonathan D.; Klotzkin, David
Abstract: The properties and yield of a distributed feedback laser depends on the values of coupling coefficient κ and many other parameters. Multisegmented distributed feedback devices (consisting of grated and ungrated areas, quarter‐wave‐shifts, and potentially other features other) are becoming more common and have advantages over uniform grated devices. A multi‐segmented transfer matrix model is used to model the spectra, yield, and slope efficiency of multisegment and uniform distributed feedback lasers. The results give an excellent match to measured spectra of partially grated, quarter‐wave‐shifted, and uniform devices, and qualitatively agree with experimental data on the distribution of slope efficiency in devices. A study on partial grated devices suggested they may have advantages in single mode yield compared to uniformly grated devices. This method (and the specific software tool Glaparex) can be used to control device parameters in manufacturing and to optimize laser designs design.